2021
DOI: 10.1097/ju.0000000000001855
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Downstaging and Survival Outcomes Associated with Neoadjuvant Chemotherapy for Variant Histology Muscle Invasive Bladder Cancer

Abstract: Purpose: Patients with muscle invasive bladder cancer (MIBC) of variant histology have a poor prognosis. It is unclear if neoadjuvant chemotherapy prior to radical cystectomy is associated with pathological downstaging or improved overall survival (OS) for patients with variant histology. Our objective was to assess for associations between receipt of neoadjuvant chemotherapy, pathological downstaging and OS for patients with variant histology MIBC. Materials and Methods: Patients were identified in the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Of those, 67% harbored non-organ-confined disease. To the best of our knowledge, this is the second largest study examining such patient population 13 . The majority of studies addressing SBC relied on small populations: from 15 to 40 patients [6][7][8][9][10] on series of comparable or even larger size than the current series.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Of those, 67% harbored non-organ-confined disease. To the best of our knowledge, this is the second largest study examining such patient population 13 . The majority of studies addressing SBC relied on small populations: from 15 to 40 patients [6][7][8][9][10] on series of comparable or even larger size than the current series.…”
Section: Discussionmentioning
confidence: 98%
“…Most studies addressing this topic are limited by small sample size (from 15 to 40 patients) [6][7][8][9][10] . Conversely, three existing large scale populationbased studies originating from the National Cancer Database (NCDB) (155, 304, and 501 patients), are all invariably limited by lack of information on cancer-specific mortality (CSM) [11][12][13] . This methodological shortfall critically undermines their observations, since an important proportion of non-metastatic SBC patients treated with RC, die of non-cancer-related causes.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the data regarding response to systemic chemotherapy from single/multicenter observational studies is not robust and often conflicting. Other published literature such as a retrospective cohort of non-metastatic cases from the National Cancer Database (NCDB) show that use of NAC correlates with higher likelihood to achieve pathologic complete response or downstaging prior to RC, whereas patients who did not receive NAC had very low rates of pCR (<6%) and downstaging (<10%) for all histologic variants (65).…”
Section: Glandular Differentiationmentioning
confidence: 99%
“…Hajiran et al (14) was the only study to compare the survival benefit of NAC between the three groups of conventional UC, UC with VH and UC with variant differentiation (squamous or glandular); here survival benefit with NAC was only achieved in conventional UC and UC with VH. A possible explanation for this apparent lack of survival benefit for NAC in variant differentiation was offered by Chakiryan et al (65). It was suggested that these patients may appear not benefit from NAC, despite significant pathological downstaging, because of generally more favorable outcomes.…”
Section: Glandular Differentiationmentioning
confidence: 99%
“…There were 14 studies evaluating the role of NAC for VH (8,10,11,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Six were populations-based studies, seven studies came from different centers, and one study was based on both center and SEER.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%